Inclination to infidelity and ways of loving in university students - Condori Yanapa, Carla Maité (2022)
Objective: to determine the relationship between the inclination to infidelity and the ways of lovingin university students. Methodology: non-experimental design, quantitative approach, correlationaltype, cross-sectional. The population consisted of 195 university students, with ages ranging from 17to 36 years, the sampling was non-probabilistic for convenience. Results: a significant correlationwas found between the inclination to infidelity and the ludus and mania love styles (p <0.05), however,no significant relationship was found with the love styles: Eros, storge, pragma and agape (p> 0.05).Conclusion: there is a significant relationship between the tendency to infidelity and the styles of love,ludus and mania, since the behaviors of these types of love tend to ephemeral, insecure love, with littlecommitment.